If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + -7 = 5 + -3x Reorder the terms: -7 + X = 5 + -3x Solving -7 + X = 5 + -3x Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + X = 5 + 7 + -3x Combine like terms: -7 + 7 = 0 0 + X = 5 + 7 + -3x X = 5 + 7 + -3x Combine like terms: 5 + 7 = 12 X = 12 + -3x Simplifying X = 12 + -3x
| 96x/3=11x/4+6 | | x^4n-5x^2n+4=0 | | 11/10m+2=7/6m+4/3 | | 2x+-6=6+-4x | | 540=b+(b+45)+90+90+3/2b | | 2(1/3w+1/4)=4+1/4w | | 30-26X=20 | | 9x+-2=6x+7 | | 7-1/2x=15 | | 3(4x+2)=9 | | b(b-3)=12 | | -2(t-3)-t-4=-3(t+5)+5 | | X-15=495 | | 4x+-8=2x+10 | | 7+3x=-1 | | -3t+2=-3t-10 | | x/2=0 | | 2x-7+5x+1=23 | | 9(v+1)-3v=2(3v+2)-10 | | y-9/y^2-y+9/6y | | 5x-3+2x=13-x | | -2/3x=-5 | | -3a-a=-4 | | 6(2+4)-1/2*3+1= | | -(2x-7y+7)= | | b+13/2=-5b/3 | | -22=5x+6x | | 6y-6(3y-11)= | | 2v+7v=-9 | | 13x-7=3(4x+5)-8 | | x-21/2 | | -11+51=-5(x+2) |